Hybrid endovascular and surgical approach for mycotic pseudoaneurysms of the extracranial internal carotid artery. (19th November 2014) - Mazzaccaro, Daniela; Stegher, Silvia; Occhiuto, Maria Teresa; Malacrida, Giovanni; Righini, Paolo; Tealdi, Domenico G; Nano, Giovanni
Objectives: Mycotic pseudoaneurysms of the extracranial internal carotid artery are rare, and their management often represents a challenge, but treatment is necessary due to the high risk of rupture and distal brain embolization. Systemic antibiotics associated with open surgical excision of the infected tissues and carotid reconstruction using autologous grafts are the treatment of choice. The use of endovascular techniques still remains controversial in infective fields; however, it can be an attractive alternative in high-risk patients or more often as a "temporary" solution to achieve immediate bleeding control for a safe surgical reconstruction. Methods: We discuss the unusual case of an extracranial right internal carotid artery mycotic pseudoaneurysm following methicillin-resistant Staphylococcus aureus infection, in a patient with poor general conditions. Results and Conclusion: The lesion was successfully treated using a hybrid endovascular and surgical procedure.